Plato and Xenophon : comparative studies - Danzig, Gabriel, 1961- (Mnemosyne supplements : monographs on Greek and Latin language and literature,, 2018)
Plato and Xenophon are the two students of Socrates whose works have come down to us in their entirety. Their works have been studied by countless scholars over the generations; but rarely have they been brought into direct contact, outside of their use in relation to the Socratic problem. This volume changes that, by offering a collection of articles containing comparative analyses of almost the entire range of Plato's and Xenophon's writings, approaching them from literary, philosophical and historical perspectives.